Lateral load behavior of RC buildings exposed to fire: case study - Vail Karakale; Ramadan E. Suleiman; Fathi M. Layas (Journal of Asian Architecture and Building Engineering, 2023)
Fire damaged reinforced concrete buildings are often made usable by performing non-structural and cosmetic repairs. These types of repairs do not guarantee the safety of such buildings under the effect of future lateral loads, such as earthquakes. In this paper, an evaluation of the lateral load response of an RC fire damaged – building in Libya is presented. The building was used as a courtyard for the public and the fire visibly damaged some of its columns and beams. Material tests were conducted in situ and in the laboratory to evaluate the material strength of the building after the fire. Then, lateral load carrying capacity of the building before and after the fire was evaluated. Analysis results show that up to one-hour fire duration the building does not lose a considerable amount of its lateral strength; however, at about two and half hours fire duration, it lost about 30 percent of its lateral load carrying capacity. Lastly, analytically predicted residual strength material properties are in good agreement with material test results.